2018
DOI: 10.18004/investig.agrar.2018.diciembre.146-151
|View full text |Cite
|
Sign up to set email alerts
|

In vitro compatibility of Trichoderma spp. with fungicides commonly used in cocoa ( Theobroma cacao L.)

Abstract: Compatibilidad in vitro de Trichoderma spp. con fungicidas de uso común en cacao (Theobroma cacao L.) In vitro compatibility of Trichoderma spp. with fungicides commonly used in cocoa (Theobroma cacao L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…has been reported by several authors [23]. Terrero et al [24] reported the compatibility of Trichoderma species with azoxystrobin and copper hydroxide fungicides, and Ruano et al [25] implemented the use of Trichoderma spp. and the fungicide fluazinam (in concentrations of 0.01 and 0.05 mg L −1 ) for the control of Rosellinia necatrix in avocado plants.…”
Section: Introductionmentioning
confidence: 85%
“…has been reported by several authors [23]. Terrero et al [24] reported the compatibility of Trichoderma species with azoxystrobin and copper hydroxide fungicides, and Ruano et al [25] implemented the use of Trichoderma spp. and the fungicide fluazinam (in concentrations of 0.01 and 0.05 mg L −1 ) for the control of Rosellinia necatrix in avocado plants.…”
Section: Introductionmentioning
confidence: 85%
“…It is only with good agricultural practices that chemical and biological interventions are cost-effective, because cultural methods alone are inadequate to control FPR (Bateman et al, 2005). Several studies report the use of fungicides as a tactic within a FPR disease management in cacao farms (Anzules et al, 2019;Bailey et al, 2018;Bateman et al, 2005;Krauss et al, 2010;Terrero Yépez et al, 2018;Torres De La Cruz et al, 2013). In this context, the lack of cacao resistant clones (Yamashita & Fraaije, 2018;Zhao et al, 2019), high morphological and molecular diversity of pathogen (Maridueña-Zavala et al, 2016), and the disease development due to climatic variables (Leandro-Muñoz et al, 2017) make it necessary to develop programmed applications of fungicides.…”
Section: Introductionmentioning
confidence: 99%